Bangladesh and SAARC : issues, perspectives, and outlook - Iftekharuzzaman; Ahmed, Imtiaz, 1958-; Bangladesh Institute of International and Strategic Studies (Dhaka : Academic Publishers, 1992)
Papers presented at a seminar held on 23-24 August 1992.
"Bangladesh Institute of International and Strategic Studies"--T.p. verso.
Includes bibliographical references.
Keywords: South Asian Association for Regional Cooperation -- Congresses; South Asia -- Relations -- Bangladesh -- Congresses; Bangladesh -- Relations -- South Asia -- Congresses